2003
DOI: 10.1101/lm.53503
|View full text |Cite
|
Sign up to set email alerts
|

Audiospatial and Visuospatial Working Memory in 6–13 Year Old School Children

Abstract: The neural processes subserving working memory, and brain structures underlying this system, continue to develop during childhood. We investigated the effects of age and gender on audiospatial and visuospatial working memory in a nonclinical sample of school-aged children using n-back tasks. The results showed that auditory and visual working memory performance improves with age, suggesting functional maturation of underlying cognitive processes and brain areas. The gender differences found in the performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
129
1
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(144 citation statements)
references
References 40 publications
7
129
1
7
Order By: Relevance
“…Overall, these studies indicate that adult females demonstrate more accurate SWM performance than adult males (Barnfield, 1999;Duff & Hampson, 2001), but males tend to show faster reaction times (Loring-Meier & Halpern, 1999). One investigation suggested a similar profile of gender differences for SWM performance in children that diminishes towards adolescence (Vuontela et al, 2003), and another SWM study in adolescents found no performance differences between the genders (Barnfield, 1999). Although the pattern of findings is somewhat difficult to interpret based on the different tasks and samples used across studies, it does suggest that gender discrepancies in SWM performance may vary based on visuospatial processing demands and stage of development.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Overall, these studies indicate that adult females demonstrate more accurate SWM performance than adult males (Barnfield, 1999;Duff & Hampson, 2001), but males tend to show faster reaction times (Loring-Meier & Halpern, 1999). One investigation suggested a similar profile of gender differences for SWM performance in children that diminishes towards adolescence (Vuontela et al, 2003), and another SWM study in adolescents found no performance differences between the genders (Barnfield, 1999). Although the pattern of findings is somewhat difficult to interpret based on the different tasks and samples used across studies, it does suggest that gender discrepancies in SWM performance may vary based on visuospatial processing demands and stage of development.…”
Section: Introductionmentioning
confidence: 89%
“…Although adult studies have demonstrated a general spatial information processing advantage for males over females that emerges with increasing age (Voyer et al, 1995), this is primarily a result of differences in active spatial processing (e.g., spatial rotation or manipulation) (Vecchi & Girelli, 1998), which is often not required in traditional n-back or delayed matching working memory tasks. Studies of SWM abilities suggest gender differences for accuracy and reaction time in children (Vuontela et al, 2003) and adults (Barn-field, 1999;Duff & Hampson, 2001;Loring-Meier & Halpern, 1999). Overall, these studies indicate that adult females demonstrate more accurate SWM performance than adult males (Barnfield, 1999;Duff & Hampson, 2001), but males tend to show faster reaction times (Loring-Meier & Halpern, 1999).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In this study, the time to perform the task was measured and reflected processing speed. (Ciesielski et al, 2006;Vuontela et al, 2003). This task examines the central executive component of working memory and was adapted for children from Dobbs & Rule (1989).…”
Section: Procedures and Instrumentsmentioning
confidence: 99%
“…To better understand this relationship between executive components and the clinical paradigms developed for their assessment, exploratory correlational studies have become important for initial discussions of the interface among the different executive subprocesses involved in the different steps of the execution of a neuropsychological task (Ciesielski, Lesnik, Savoy, Grant, & Ahlfors, 2006;Davidson, Amso, Anderson, & Diamond, 2006;Hughes & Graham, 2008;Kray, Kipp, & Karbach, 2009;Kristensen, 2006;Mazzocco & Klover, 2007;McAuley & White, 2010;Vuontela, Steenari, Carlson, Koivisto, Fjallberg, & Aronen, 2003). Some studies highlighted an important relationship among executive components, such as between inhibition and the central executive of working memory.…”
Section: Introductionmentioning
confidence: 99%